The promoted growth of genetically lodgepole and white spruce in Western Alberta compared to natural stocks - Park, Matthew (My University, 2022)
Forest regeneration has been an important focus across Alberta and the rest of Canada over recent decades. An industrial company in Alberta known as Canfor have recently began regenerating using a genetic stock where a seed bank has been used from an orchard to create the tallest, strongest and fastest growing trees in the vicinity. Although the trees are genetically improved they are not considered GMO’s simply because they have been bred properly and have not endured any unnatural tampering. GMO’s are considered genetically modified organisms which have had modification done on them. Orchard trees are improved be breeding the best mother and father within the orchard for cone production and reproducing with these cones. The idea behind this stock is to speed up the reforestation process in post-harvest stands to shorten the harvest rotation and to recreate habitat in a shorter period of time. The results from the findings show a direct comparison between the genetic stock and the natural stock at different age classes from seedling to 5 years of age. The results derived from this experiment are significant to forestry due to its potential for rapid growth which will speed up block regeneration and harvest rotations noticeably in the future.
Keywords: Forest regeneration; Tree improvement; Climate change & forest adaptation